2013
DOI: 10.1080/14616734.2013.797266
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment interviews of women from low-risk, poverty, and maltreatment risk samples: comparisons between the hostile/helpless and traditional AAI coding systems

Abstract: The main aim of this study was to investigate the correlates of a Hostile-Helpless (HH) state of mind among 67 women belonging to a community sample and two different at-risk samples matched on socio-economic indicators, including 20 women from low-SES population (poverty sample) and 15 women at risk for maltreatment being monitored by the social services for the protection of juveniles (maltreatment risk sample). The Adult Attachment Interview (AAI) protocols were reliably coded blind to the samples' group st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Also, childhood loss and trauma were found to be differentially associated with maternal unresolved and hostile-helpless states of mind (Lyons-Ruth, Yellin, Melnick, & Atwood, 2003). How both coding systems (Lyons-Ruth, Bronfman, & Parsons, 1999;Main et al, 2003) are interrelated was studied in low risk, poor and maltreating mothers (Frigerio, Costantino, Ceppi, & Barone, 2013). The authors found HH profiles not to overlap with Ud, CC and E3 categories.…”
Section: Introductionmentioning
confidence: 96%
“…Also, childhood loss and trauma were found to be differentially associated with maternal unresolved and hostile-helpless states of mind (Lyons-Ruth, Yellin, Melnick, & Atwood, 2003). How both coding systems (Lyons-Ruth, Bronfman, & Parsons, 1999;Main et al, 2003) are interrelated was studied in low risk, poor and maltreating mothers (Frigerio, Costantino, Ceppi, & Barone, 2013). The authors found HH profiles not to overlap with Ud, CC and E3 categories.…”
Section: Introductionmentioning
confidence: 96%
“…Unresolved states of mind in relation to loss or abuse are considered indicators of disorganized attachment (Holmes, 2004;Lyons-Ruth et al, 2005). A review of 13 empirical studies supported the centrality of disturbed attachment for BPD: disorganized attachment was estimated at between 32% and 89%, which was raised to 100% among BPD patients with history of trauma (Agrawal, Gunderson, Holmes, & Lyons-Ruth, 2004;Frigerio, Costantino, Ceppi, & Barone, 2013). In a sample of adults and adolescents, Westen and colleagues (2006) examined the relationship between attachment and personality pathology and found significant correlations between BPD and disorganized attachment (0.44 for adolescents and 0.48 for adults).…”
Section: Introductionmentioning
confidence: 99%
“…HH states of mind have been validated in relation to prior experiences of abuse (Lyons–Ruth, Melnick, Atwood, & Yellin, 2003), in relation to disrupted communication between parent and child (Lyons-Ruth, Yellin et al, 2005), in relation to infant disorganized attachment (Melnick, Finger, Hans, Patrick, & Lyons-Ruth, 2008; Lyons-Ruth, Yellin et al, 2005), and in relation to maternal abuse or neglect of her child (Barone, Bramante, Lionettia, & Pastore, in press; Frigerio, Costantino, Ceppi, & Barone, 2013; Milot, Lorent, St-Laurent, Bernier, Tarabulsy, Lemelin, & Éthier, 2014). …”
mentioning
confidence: 99%